IMPLEMENTATION OF PRACTICAL E-LEARNING MODEL ON K.A.P (PSYCOMOTOR AFFECTIVE COGNITIVE) IN MIDWIFE STUDENTS IN THE ERA OF THE COVID-19 PANDEMIC - Kartikasari, M Nur Dewi; Parwatiningsih, Sri Anggarini; Hardiningsih, Hardiningsih; Fatsena, Rizka Adela; Yunita, Fresthy Astrika; Ropitasari, Ropitasari; Hutomo, Cahyaning Setyo; Megasari, Anis Laela; Khuzaiyah, Siti (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: The outbreak of the corona virus (Covid-19) poses challenges for educational institutions, especially those based on clinical practice skills. E-learning is one of the best solutions for distance learning to protect students and teaching staff from the transmission of the Covid-19 virus. The DIII Midwifery Study Program curriculum consists of 40% theory and 60% practice. The study program manager determines practical learning using learning videos. The purpose of this study was to determine the effect of the practical e-learning model on K.A.P (Affective Psychomotor Cognitive) in midwifery students in the era of the Covid-19 pandemic.Methods: This reseach was a cross-sectional conducted on May-July, 2021. Cognitive assessment used multiple choice questions (MCQ), affective assessment used a self-assessment scale questionnaire that was valid and reliable (0.877> 0.235), Student psychomotor assessment was carried out using Skills checklist assessment sheet.Result: The results showed the significance value of each variable (0.001 <0.05) which means that there is an influence of the practical e-learning model on the cognitive, affective and psychomotor domains of students in the course of maternity midwifery care.Conclusion: There is an effect of practical e-learning model on the cognitive, affective, and psychomotor domains of the students after the practical of e-learning model